(3GdaQGFO hGdbdGFOs - (3GdQTjO GdhWhGW , eMeO Hf eMeO Hf YHO GdLdjd Hf YHO Gdedc GdYeQj GdHdNj, QTjO GdOjf CHh HcQ,J (B573 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYGdi GdcHjQ CeG HYO aEf CMb eG fWb Hg GddSGf hCYQH Yfg GdHjGf s
(3BNQgG (B:s
(3bHd (B: (3Jcde QLd ai eLdS GHf YHGS aNdW abGd GHf YHGS HcdGe eKdc QRb GdUHQ GdeMHI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B25 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B229s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs